Prospek Bank Syari'ah Studi Pendahuluan Pandangan Mahasiswa STAIN Malang - Djakfar, Muhammad (ULUL ALBAB Jurnal Studi Islam, 2002)
This research is to describe the students' opinion on shariah banks in Malang. In this qualitative research, in-depth interview and documentary analysis were used to obtain the needed data. The findings showed that (I) the shariah banks were not sufficiently socialized, (2) the respondents stated that the system applied by the shariah banks were not different from the conventional ones, (3) the respondent supported the existence of these syariah banks as these syariah banks were intended to apply Islamic principles. The three opinions were determined by the respondents' social interaction, advertisement of bank, or academic activities (seminar, workshop, etc) which offered the relevant topics on syariah banks.